Factors Related to the Compliance of Elderly Diabetes Mellitus Patients with Blood Glucose Control - Adi Buyu Prakoso; Ady Irawan; Azizah Sonia Hapsari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes Mellitus is often found in the elderly. This condition causes the elderly to be in a risk group with biological risk characteristics or risks related to age, social and environmental risks and behavioral or lifestyle risks. The high number of Diabetes Mellitus sufferers that continues to increase, of course, results in many complications that occur in Diabetes Mellitus sufferers. Patients who are unable to control their blood sugar levels well are at high risk of complications and must be aware of hyperglycemia. This study aims to determine factors related to blood glucose control in the elderly. Compliance with blood glucose control in the elderly can reduce the risk of complications and early detection of health workers in handling diabetes mellitus sufferers in the elderly. The type of design in this study is quantitative with an analytical observational method. The population in this study was the elderly in the Baki Health Center work area with a total of 78 elderly respondents with a total sampling. This study uses a cross-sectional design. The population in this study was conducted on the elderly in the Baki health center work area with a sampling method, namely accidental sampling. The results of the bivariate analysis using the chi square statistical test of the related factors are the level of knowledge (P = 0.018), family support (P = 0.001), motivation (P = 0.012) and family income (P = 0.025). The results of multivariate analysis using logistic regression analysis showed that the most related factor was family support with an OR value of 0.28. The conclusion in this study is that the most related factor to blood glucose control compliance in the elderly is family support.